Replicating "Predicting the present with Google trends" by Hyunyoung Choi and Hal Varian (The Economic Record, 2012) - Tom Coupé (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper, the author describes different ways in which one can replicate a paper and illustrate them by applying them to the study by Choi and Varian (Predicting the Present with Google Trends, The Economic Record 2012).
Keywords: A1; C1; C8; C53; 330; Replication